Core Self-Evaluation and Work Engagement: Moderated Mediation Model of Career Adaptability and Job Insecurity - Yoo, Kieun; Lee, Ki-Hak (Frontiers in Psychology, 2019)
This study examined the moderated mediation roles of job insecurity through career adaptability on the relation between core self-evaluation and work engagement. A total of 335 Korean full-time employees who had been employed for less than three years responded to the questionnaire survey. Excluding missing data and outliers, data from 324 participants (men=82, women=242) were analyzed using SPSS 25.0 and SPSS PROCESS Macro. The results indicated that job insecurity moderated the indirect association between core self-evaluation and work engagement via career adaptability. This study further expanded the understanding of newly employed employees' adaptation. Implications and limitations of the study and suggestion for further study were discussed.